2006
DOI: 10.3139/146.101387
|View full text |Cite
|
Sign up to set email alerts
|

Residual-stress-induced subsurface crack nucleation in titanium alloys

Abstract: This investigation has considered the influence of heat treatment, environment and residual stress level on the response of titanium alloys to mechanical surface treatment. It has been shown that the high cycle fatigue benefits to be gained by mechanical surface treatment will depend upon all of these variables. For example, shot peening of Ti–6Al–7Nb a/b solution treated, water quenched and aged condition results in a substantial increase in the high cycle fatigue performance in laboratory air. In contrast, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Roller burnishing of Ti-10V-2Fe-3Al beta alloy induced deeper and higher magnitude residual stress compared to shot peening. In roller burnishing of LCB beta alloy, higher the rolling pressure, deeper was the site for fatigue crack nucleation [27]. In Beta C (Ti-3Al-8V-6Cr-4Mo-4Zr) alloy, deep rolling ended up with deeper residual stress distribution compared to shot peening, but the magnitude of the residual stress remained high for the shot peened sample.…”
Section: Mechanical Surface Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Roller burnishing of Ti-10V-2Fe-3Al beta alloy induced deeper and higher magnitude residual stress compared to shot peening. In roller burnishing of LCB beta alloy, higher the rolling pressure, deeper was the site for fatigue crack nucleation [27]. In Beta C (Ti-3Al-8V-6Cr-4Mo-4Zr) alloy, deep rolling ended up with deeper residual stress distribution compared to shot peening, but the magnitude of the residual stress remained high for the shot peened sample.…”
Section: Mechanical Surface Modificationmentioning
confidence: 99%
“…However, CP Ti is associated with lower wear resistance and Ti-6Al-4V when implanted inside the body releases Al and V ions which can Processing of Beta Titanium Alloys for Aerospace and Biomedical Applications DOI: http://dx.doi.org /10.5772/intechopen.81899 lead to severe neurological disorders and allergic reactions. Moreover, the elastic modulus values of these alloys (~110 GPa) are almost four times than that of human cortical bone (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) which can lead to stress shielding effect. This led to the development of β-Ti alloys composed of non-toxic elements and their inherent lower elastic modulus assists in reducing the stress shielding effect when used for orthopaedic applications [3].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Furthermore, the balancing tensile residual stress is about 100 MPa and 50 MPa after SP and BB, respectively. It may be argued that the observed transition in fatigue crack nucleation site from surface to subsurface in mechanically surface treated conditions results from the presence of a high tensile residual stress at a location below the specimen surface [1]. As a result, the fatigue performance is also improved in BB samples compared to SP material.…”
Section: Residual Stressesmentioning
confidence: 99%
“…Some studies have been carried out to investigate the influence of mechanical surface treatments on the fatigue performance of Ti-2.5Cu. It was found that the fatigue endurance stresses was improved by 45% after SP [1][2][3] and 60 % after BB [3] in rotating beam loading (R = -1). Such improvements have revealed that the failure is associated with subsurface fatigue crack nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that fatigue failure in mechanically surface treated titanium alloys within the low stress, high cycle regime is often associated with subsurface (quasi-vacuum) fatigue crack nucleation. This phenomenon may be related to the presence of process-induced tensile residual stresses necessarily present below the mechanically treated surface and required to balance the outer process-induced residual compressive stresses [5][6][7][8][9]. The residual stresses induced by mechanical surface treatments have been measured by applying ED using synchrotron radiation (10 to 80 keV).…”
Section: Introductionmentioning
confidence: 99%